A reassessment of traditional lexicographical tools in the light of new corpora: sports Anglicisms in Spanish - Balteiro, Isabel (International Journal of English Studies, 2011)
There is no question nowadays as to the international and powerful status of English at a global scale and, consequently, as to its presence in non-English speaking countries at different levels. Linguistically speaking, English is one of the languages which have mostly influenced Spanish throughout its history and especially from the late 1960s. In this study, the impact of English on Spanish is considered in the language of sports; particularly, sports Anglicisms and false Anglicisms are analysed. Due attention is paid to the different forms that an Anglicism may adopt and to which of those forms are more widely accepted or rejected by prescriptivists and speakers at large, in the light of a contrastive analysis of their appearance in the Nuevo diccionario de anglicismos, the Diccionario de la Real Academia Española and the Corpus de Referencia del Español Actual.